ナンキョク ラングホブデ ライチョウサワ ニ オケル センルイ ノ ハンショクタイ バンク - 鮎川, 恵理; アユカワ, エリ; 伊村, 智; イムラ, サトシ; 神田, 啓史; カンダ, ヒロシ; Ayukawa, Eri; Imura, Satoshi; Kanda, Hiroshi (2002)
P(論文) 南極ラングホブデ雪鳥沢の植生周辺での蘚類の繁殖体バンクの分布, 種構成, 繁殖体の発芽能力を土壌培養により調べた。土壌サンプルを12週間にわたり培養した結果, 菌類, 藻類, 蘚類の出現が確認された。最も多く出現した蘚類は調査地に生育するオオハリガネゴケBryum pseudotriquetrumであった。調査地に生育していなかったヤノウエノアカゴケCeratodon purpureus, キョクチセンボンゴケPottia heimiiのシュートの出現も確認された。出現した蘚類シュートの大半はシュート断片から発芽しており, シュート断片が栄養繁殖体として重要であると考えられた。蘚類群落に近い場所ほど数多くのオオハリガネゴケシュートが出現したことと, 調査地にはなくその上下流域に生育する二種が出現したことから, 繁殖体バンクは比較的近距離な散布を中心に, 低頻度な遠距離散布を含めた上で成立していると考えられた。 Distribution, species composition and possibilities of germination of the propagule bank of moss in Antarctic soils were investigated by cultural experiments. Soil samples were collected in the Yukidori Valley, Antarctica, and were incubated under laboratory conditions. After several weeks, fungi, algae and mosses were observed in the samples. The dominant species within the germinated moss shoots was Bryum pseudotriquetrum s. lat.; in fact, this species was the only moss species at the study site. Shoots of Ceratodon purpureus and Pottia heimii appeared rarely in the general area, but were not observed at all at the study site. Vegetative propagules such as fragments of shoots were frequently found in the soils, most of the germinated shoots sprouted from such propagules. These propagules were thought to be important for colonization at the site. A relatively large number of shoots of B. pseudotriquetrum appeared from the samples collected from the ground near the vegetation. Most of the propagules of B. pseudotriquetrum in the soils were thought to be dispersed from nearly communities, whereas some propagules such as C. purpureus and P. heimii were thought to be dispersed from more distant moss communities. departmental bulletin paper